Memorandum on maternal mortality - Labour Party (Great Britain). Advisory Committee on Public Health
1928-07 1928 1920s 10 pages - 6 - officer, for a period of three months, during one month of which he should perform the duties of an intern student in a lying-in hospital or ward; he should attend during the period twenty cases of labour, under adequate supervision. Extern or district maternity work should not be taken until the student has personally delivered at least five cases in the lying-in hospital or ward to the satisfaction of his teacher. This is not yet put into effect (1928). 2. The Medical Student - is available for attendance at confinements when sent by the Hospital, but may never have seen a case delivered before, and may attend with or without a midwife. The only medical aid he can summon is that of the newly qualified resident obstetric officer of his hospital, who in turn can obtain the services of an obstetric specialist. 3. The Midwife. A fully-trained nurse can obtain the certificate of the Central Midwives Board after six months, or for those previously untrained a year's midwifery training is necessary. If she needs assistance in the course of her work, she may summon a fully qualified practitioner, but not a specialist. 4. The student midwife. After attending confinements with a trained midwife in the course of her training, may attend alone and may summon a trained midwife in case of need. 5. The Handywoman - is usually a kindly neighbour; whatever her motives, she must not attend the patient habitually and for gain. She is a source of much trouble. 6. Home Helps. Domestic help in the home during confinement may be provided by the Local Authorities under the Maternity and Child Welfare Act (1918). Only 56 Local Authorities have made use of this power. A register is kept of suitable women to act in this capacity. (c) Institutions. There are a number of Maternity Institutions recognised by the Minster of Health, either directly or indirectly, for purposes of grants as follows (1926); Voluntary 81 with 1,423 beds Municipal 68 " 867 " Total 149 " 2,290 " 292/824/1/121